The Artistic Infant Directed Performance: A Mycroanalysis of the Adult’s Movements and Sounds - Español, Silvia Ana (2015)
Intersubjectivity experiences established between adults and infants are partially determined by the particular ways in which adults are active in front of babies. An important amount of research focuses on the “musicality” of infant-directed speech (defined melodic contours, tonal and rhythm variations, etc.) and its role in linguistic enculturation. However, researchers have recently suggested that adults also bring a multimodal performance to infants. According to this, some scholars seem to find indicators of the genesis of the performing arts (mainly music and dance) in such a multimodal stimulation. We analyze the adult performance using analytical categories and methodologies of analysis broadly validated in the fields of music performance and movement analysis in contemporary dance. We present microanalyses of an adult-7 month old infant interaction scene that evidenced structural aspects of infant directed multimodal performance compatible with music and dance structures, and suggest functions of adult performance similar to performing arts functions or related to them.